MEDIA PENGELOLAAN UANG UNTUK MENINGKATKAN FINANCIAL LITERACY PADA ANAK USIA SEKOLAH DASAR - Mulyati, Budi; Nurlaili, Fitri (Metodik Didaktik : Jurnal Pendidikan Ke-SD-an, 2020)
This research was a classroom action research which aimed to find out; 1) the learning activities used money management media used role playing model, 2) the students financial literacy, 3) the obstacles during the preparation until implementation of learning activities. The subjects of the research were the students at grade 4 at Ciruas public elementary school 3 and Sempu public elementary school 2 Serang. The data collection used test and observation. The data analysis used quantitative descriptive data. Based on the results, the results showed that 1) At Sempu Public Elementary School 2, the learning activity at the 1st meeting was 62.5% and at the 2nd meeting increased up to 86.53%. At Ciruas Public Elementary School 3, the learning activity at 1st meeting was 70.83% and at the 2nd meeting increased up to 94.23%. 2). The financial literacy at Sempu Public Elementary School 2 was 90.90% exceeded the minimum criteria value and at Ciruas Public Elementary School 3 was 84.37% exceeded the minimum criteria value. 3). The obstacles were there were some students who were not fluently in reading and writing, students absence and reduced students focus at the end of learning.